PENYULUHAN KESEHATAN TENTANG HIPERTENSI DI WILAYAH RT 03 KELURAHAN MURNI - Vevi Suryenti Putri; Maimaznah Maimaznah; Sumiyati Sumiyati; Yuliana Yuliana; Rica Meiliani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Hypertension is a disease that is more common because of unhealthy lifestyle, community RT 03 sub pure many suffer from hypertension because of lack of attention to the pattern of their lives, the public is less aware of the impact of hypertension so that even know they suffer from hypertension still doesn't change the style of life and rarely check the health.Based on the assessment done through interviews, observation and questionnaires showed problems in RT 03 sub Pure that cadres said the disease experienced by residents of RT 03 is hypertension, 63,63% of people of mature age and the elderly suffer from hypertension.Of counseling that we convey expected that citizens can implement a healthy lifestyle in everyday life as well as being able to control a wide range of health problems associated with a healthy lifestyle such as exercise regularly, low-fat diet, and do regular inspections. Follow-up plan of extension activities about hipetensi is coordinated with the health center to do counseling about hypertension by involving the cadres in the village pure and also coordinate with the health center to run the program health checks.